Co-expression of LPHN3 and NKX3.1 as a predictive biomarker for metastasis in breast cancer - Ramsha Khan; Mohiuddin Alamgir; Nehad Khan; Mohammad Bilal Khan; Farah Fatima Abbas; Saba Kamil (Journal of the Pakistan Medical Association)
Objectives: To assess latrophilin-3 (LPHN3) and Homeobox protein (NKX- 3.1) protein expression in breast cancer, and the association with metastasis.